POLA PENGEMBANGAN PERIKANAN BUDIDAYA TAMBAK BERBASIS KARAKTERISTIK LINGKUNGAN DI PESISIR ANTARA SUNGAI BOGOWONTO KABUPATEN KULONPROGO DAN SUNGAI JALI KABUPATEN PURWOREJO - , Bambang Triyatmo, Ir.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research have been done in the coastal area between the Bogowonto River Kulonprogo Regency and Jali (Cokroyasan) River Purworejo Regency. In the coastal area, the Bogowonto River and Jali River are connected by Pasir- Jati River. The aim of this study was to determine the development patterns of pond aquaculture. The pond aquaculture development patterns were studied based on the characteristics, usage, and the degree of suitability coastal environments. The concepts of the development were based on the compatibility fish species and applied technological approaches. The research were carried out by employing map interpretations, surveys, observations, and interviews. The coastal environment characteristics were observed including landform, slope, texture and pH of soil, water level fluctuations, salinity and pH of water, and landuse parameters. The coastal environment usage was studied in order to relate aquaculture ponds, agricultural cultivation, and Pasir-Jati River fisheries. The suitability of coastal environments for aquaculture were evaluated based on the weighting and scoring parameters. The results revealed that the pattern of aquaculture ponds to be developed in sand dunes area should use water pumped directly from the sea for culturing white shrimp (Litopenaeus vannamei) and black tiger shrimp (Penaeus monodon) by applying a semi-intensive and/or intensive technologies. The pattern of aquaculture ponds to be developed in swale should use water from the Pasir-Jati River for culturing milkfish (Chanos chanos), mullet fish (Mugil sp.), tilapia (Oreochromis sp.) by applying an extensive technology. During one year period, pond aquaculture in this area could be operated in three patterns based on the season and waters condition, which were in the period of April-July (dry season), August-November when the Bogowonto and Jali estuarines were closed by sand sediment, and December- March (rainy season).